Fracture toughness evaluation of axially-cracked tubular thin-walled specimens of Zircaloy-4 and its implications for integrity analysis of nuclear fuel clad. (April 2020) - Syed, A.; Samal, M.K.; Chattopadhyay, J.; Dutta, P.
Highlights: Fracture experiments were conducted using axially-cracked tubular fuel clad specimens. Using conical mandrel, loading on fuel clad by an hourglass pellet has been simulated. Frictional force plays an important role for estimation of J-R curves of specimens. Value of crack initiation toughness J0.2 is lower for specimens with higher a/W ratio. Crack initiation toughness is nearly insensitive to specimen length and mandrel angle. Abstract: As nuclear fuel clad is a thin-walled and small diameter tube, it is not possible to machine standard ASTM specimens from these tubes in order to conduct the fracture tests. In this work, fracture experiments have been conducted using a different type of specimen (which is machined from the tubular clad of Zircaloy-4) and a test setup. Initial cracks in the axial direction have been machined in these tubular specimens and the cracked tubes have been loaded with a conical mandrel. The conical mandrel, when pushed into the cracked specimen, simulates the loading which is similar to that induced by the hourglass-shaped fuel pellet on fuel clad during the postulated reactivity-initiated-accident scenarios. By changing the mandrel angle as well as the specimen geometry, different magnitudes of crack-tip constraints are induced in the experiments and these, in turn, influence the crack initiation and propagation toughness of the axially-cracked fuel clad. In addition, simulations have been carried out using 3D elastic-plastic finite element model of the fuel clad, mandrel and their frictional contact to predict the load-displacement behavior. The crack-tip constraints of the axially-cracked specimens of different geometries have been evaluated from results of finite element analysis. The J-R curves as functions of different specimen geometry and loading conditions have been evaluated from experimental data and the differences of the fracture toughness data among the specimens have been explained in terms of variations in crack-tip constraint.